Global literacies : lessons on business leadership and national cultures : a landmark study of CEOs from 28 countries - Rosen, Robert H. (New York : Simon & Schuster, 2000)
"In Global Literacies, a team of researchers led by Robert Rosen, Ph. D., of Healthy Companies International, and Watson Wyatt Worldwide have produced the first model of international business success based on a wide-ranging landmark study of global leaders and their world-class companies. Global Literacies documents the exclusive results of a worldwide survey of over one thousand senior executives and in-depth interviews with CEOs of seventy-eight companies - companies representing 3.5 million employees in more than 200 countries, and with more than $725 billion in annual sales."--Jacket.
The search for global competitiveness. The new business reality ; The cultures of twenty-first-century business -- The four global literacies: creating a new language of business. Personal literacy: understanding and valuing yourself ; Social literacy: engaging and challenging others ; Business literacy: focusing and mobilizing your organization ; Cultural literacy: valuing and leveraging cultural differences -- The global literacies at work: solving the five universal business questions. Purpose: where are we going? ; Plan: how do we get there? ; Networks: how do we work together? ; Tools: what resources do we need? ; Results: how do we measure success? -- Becoming a globally literate leader. Your path to global literacies.
Includes bibliographical references (pages 380-384) and index.
Keywords: Chief executive officers; Leadership